Black women and breast cancer : a cultural theology - Williams, Elizabeth A., 1972- (Anthropology of well-being., 2019)
Elizabeth Williams draws on the perspectives of womanist theology and anthropology to examine how Black, American women use faith to achieve well-being after a breast cancer diagnosis. Williams portrays how these women have constructed a cultural theology of breast cancer that draws on their experiences and worldviews.